2021
DOI: 10.1155/2021/8891324
|View full text |Cite
|
Sign up to set email alerts
|

RAGE and HMGB1 Expression in Orbital Tissue Microenvironment in Graves’ Ophthalmopathy

Abstract: Graves’ ophthalmopathy (GO) is a chronic autoimmune inflammatory disorder involving orbital tissues. A receptor for advanced glycation end products (RAGE) and its ligand high mobility group box 1 (HMGB1) protein trigger inflammation and cell proliferation and are involved in the pathogenesis of various chronic inflammatory diseases. This study was aimed to evaluate RAGE and HMGB1 expression in GO to determine its potential clinical significance. To the best of our knowledge, this is the first study showing RAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In this study, we found that EMV and EMV/OV in the orbits of the TED-IM group were larger than those in the TED-NM group. These results are consistent with prior studies and generally accepted, since the impairment is caused by enlarged EM tissue infiltrated with various inflammatory cytokines [16,17]. Moreover, RFV and RFV/OV were found to be smaller in TED-IM patients.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that EMV and EMV/OV in the orbits of the TED-IM group were larger than those in the TED-NM group. These results are consistent with prior studies and generally accepted, since the impairment is caused by enlarged EM tissue infiltrated with various inflammatory cytokines [16,17]. Moreover, RFV and RFV/OV were found to be smaller in TED-IM patients.…”
Section: Discussionsupporting
confidence: 93%
“…They found an increase in HMGB1 expression that corresponded to the severity of Graves' ophthalmopathy. 11…”
Section: Introductionmentioning
confidence: 99%